ANALISIS KONTROL KUALITAS PRODUKSI BERRY COOKIES DENGAN PENDEKATAN FISHBONE DIAGRAM DI PT ABC - Risa Safitri Putri Aditya; Lilis Sulandari; Ila Huda Puspita Dewi; Mafisah Restami (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Quality control is a key managerial function in the food industry to ensure that products consistently conform to established standards. This study aims to analyze the quality control of Berry Cookies production at PT ABC, a gluten-free, dairy-free, and preservative-free cookie product, across three processing phases: preparation, main processing, and final processing. The problem examined is the recurring non-conformance of product moisture content against the company standard of 3.5%, which triggered consumer complaints regarding a rancid odor upon opening the package. A descriptive qualitative method was applied through direct observation, structured interviews with the Quality Control manager, QC staff, and production operators, as well as documentation of quality standards, standard operating procedures, and process records. Data were analyzed using a fishbone diagram limited to three categories, namely machine, method, and man (3M). The results show that the machine factor is dominated by unstable oven temperature, which dropped from 147°C to 135°C at the 35th minute of baking, and by inconsistent dough weight produced by the depositing machine during startup, reaching 16 grams against a 12-gram standard. The method factor reveals the absence of a standard operating procedure for the initial operation of the depositing machine, an oven temperature recording system that does not reflect actual field conditions, and inconsistent product temperature management prior to packaging, which causes water vapor condensation inside the package. The man factor indicates operator non-compliance with oven operating procedures, driven by insufficient training for new operators and uncontrolled overtime fatigue, together with a delayed response from the QC team. These three factors interact and jointly contribute to the moisture content deviation of Berry Cookies. Keywords:Fishbone Diagram; Gluten Free Cookies; Moisture Content; Quality Control; Standard Operating Procedure.